A Low-pass Filter with Sharp Transition and Wide Stop-band Designed based on New Metamaterial Transmission Line - L. Peng; Y. J. Qiu; X. Jiang; C. L. Ruan, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A low-pass filter (LPF) with sharp and wide stop-band was designed based on new metamaterial transmission line. Its characteristics were investigated, and found to have good low-pass performances with only one cell. The simulated results of the LPF are in good agreements with the measured results. Two measured transmission poles were observed at 1.35 GHz and 2.13 GHz. The measured 3 dB cut-off frequency is 2.38 GHz and the transmission attenuate to -20 dB at 2.62 GHz, thus, a 240 MHz width sharp transition was achieved. The measured attenuation of the stop-band is larger than 25 dB with two transmission zeros at 2.79 GHz and 5.19 GHz. A wide stop-band over 10 GHz was observed. Therefore, the proposed LPF is a good candidate for RF systems.